2020
DOI: 10.1155/2020/2659475
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Stick‐Slip Type Rotary Piezoelectric Actuator

Abstract: A novel stick-slip rotary piezoelectric actuator is designed for optical use. The actuator is proposed, fabricated, and tested with the aim of realizing both fine resolution and a long stroke. The dynamic model of the actuator is established, and simulations are performed to discover how the input driving voltage affects the stick-slip motion of the actuator. An experimental system is built to evaluate the performance of the actuator at different frequencies, voltages, and numbers of driving piezoelectric stac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Wang et al developed a kinetic friction model of the actuator and investigated the effect of the input drive voltage on the viscous slip motion of the actuator through simulation [32]. Nguyen et al used the method of dimensionality reduction to describe the frictional contact behavior of the stick-slip microactuator.…”
Section: Comprehensive Model Of Piezoelectric Stick-slip Actuatorsmentioning
confidence: 99%
“…Wang et al developed a kinetic friction model of the actuator and investigated the effect of the input drive voltage on the viscous slip motion of the actuator through simulation [32]. Nguyen et al used the method of dimensionality reduction to describe the frictional contact behavior of the stick-slip microactuator.…”
Section: Comprehensive Model Of Piezoelectric Stick-slip Actuatorsmentioning
confidence: 99%
“…As is known to all, under an external electric field, piezoelectric materials can generate deformations because of the rotation of the internal electric domain. When it comes to piezoelectric materials, piezoelectric effects are the most special functional characteristics including the direct piezoelectric effect and the converse piezoelectric effect [31][32][33][34]. When the mechanical stress is applied to the piezoelectric materials, electric charges can be produced on the electrodes of the piezoelectric materials, which is called the direct piezoelectric effect.…”
Section: Piezoelectric Effectsmentioning
confidence: 99%
“…It has been shown that the subswitching response of a number of ferroelectric materials well obey the RL. Examples include donor-doped soft Pb(Zr,Ti)O 3 (PZT) ceramics [5,27,28,30], coarse-grained undoped BaTiO 3 [31], high-Curie-temperature piezoceramics based on BiScO 3 -PbTiO 3 [24], textured (K 0.5 Na 0.5 )NbO 3 (KNN) ceramics [32], Aurivilius-type Nb-doped Bi 4 Ti 3 O 12 [31], some relaxor-ferroelectric Pb (Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 compositions [33,34] and Pb-based thin films [35,36]. It has to be pointed out, however, that even in these cases, strictly speaking, a good match between the Rayleigh model and the measured subswitching response is typically observed in a limited driving field range, sometimes referred to as the "Rayleigh range" [5,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piezoelectric motors have a variety of structures, but the mainstream of the academic circle divides them into inchworm piezoelectric motors [10][11][12], ultrasonic piezoelectric motors [13,14], and inertial impact piezoelectric motors [15][16][17][18][19]. The inertia impact piezoelectric motor uses the inertia impact of the stator vibration to generate micro displacement to realize the linear motion or rotation of the mover [20,21].…”
Section: Introductionmentioning
confidence: 99%